Evaluasi Peraturan Bupati Nomor 4 Tahun 2009 tentang Izin Usaha Pengelolaan dan Pengusahaan Sarang Burung Walet di Kecamatan Kunto Darussalam Kabupaten Rokan Hulu - Nurfadila Nurfadila; Hammed Diputra Imfyan; Zulkarnaini Zulkarnaini (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Rokan Hulu Regency in the implementation of swallow cultivation has been regulated in Rokan Hulu Regent Regulation No.4 of 2009 concerning business license management and swallow's nest business license. There are still many swallow nests that are established not in accordance with the provisions in the Rokan Hulu Regent Regulation, have not processed the swallow nest business license. Regent of Rokan Hulu, have not taken care of the license and there are still people who do not know that there is a regulation on swallow nests. do not know that there are rules governing the establishment of swallow nests. swallow's nest. This research aims to evaluate Regent Regulation number 4 of 2009 concerning business licenses for the management and swallow nest business license in Kunto Darussalam Subdistrict, Rokan Hulu Regency and its inhibiting factors. Rokan Hulu and its inhibiting factors. The theory used is Lester and Stewart (2000). divides policy assessment into four types. The suggested types or models are: a) Process evaluation b) Impact evaluation c) Policy evaluation, evaluation to test relevance d) Meta-evaluation. The results of this study found that there was still no maximum socialization (communication) given to the community. Facilities and infrastructure (facilities) that have not been maximized by utilizing existing websites.